2013
DOI: 10.1091/mbc.e12-11-0811
|View full text |Cite
|
Sign up to set email alerts
|

Means of self-preservation: how an intrinsically disordered ubiquitin-protein ligase averts self-destruction

Abstract: Ubiquitin-protein ligases (E3s) are often in the precarious position of ubiquitinating themselves, mediating their own destruction. The intrinsically disordered E3 San1 prevents its own autoubiquitination and degradation by minimizing Lys residues and hydrophobic stretches in its disordered regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…The protein interaction database (16,(33)(34)(35)(36) revealed the interaction of San1 with the Spt16 component of FACT that is involved in promoting transcriptional elongation (5,6). On the basis of this information, we hypothesize that San1 regulates transcriptional elongation, possibly by controlling the stability or abundance of Spt16 via ubiquitylation and proteasomal degradation.…”
Section: Resultsmentioning
confidence: 94%
“…The protein interaction database (16,(33)(34)(35)(36) revealed the interaction of San1 with the Spt16 component of FACT that is involved in promoting transcriptional elongation (5,6). On the basis of this information, we hypothesize that San1 regulates transcriptional elongation, possibly by controlling the stability or abundance of Spt16 via ubiquitylation and proteasomal degradation.…”
Section: Resultsmentioning
confidence: 94%
“…1). Because a single lysine San1 would allow for the specific monitoring of polyubiquitin chain formation without the potentially confounding effects of multi-monoubiquitylation, all naturally occurring San1 lysine residues were mutated to arginine, and a single lysine was introduced at Asn-13 because previous experiments in yeast demonstrated that N13K San1 was both autoubiquitylated and capable of binding to misfolded proteins (38).…”
Section: Resultsmentioning
confidence: 99%
“…It had previously been shown that introducing a small, hydrophobic patch in the San1 amino acid sequence resulted in increased turnover of San1 protein in yeast (38). In those experiments, the RING domain in San1 had been mutated to eliminate autoubiquitylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…San1’s ability to target misfolded nuclear proteins is attributed to large regions of intrinsic disorder within the N-and C-terminal regions of San1 [12]. These disordered regions possess multiple substrate-interaction regions within a conformationally plastic scaffold, which we propose provides San1 a broad mechanism to target many different kinds of misfolded proteins [12,35]. San1 has been found to recognize exposed hydrophobicity within its misfolded substrates that would have normally been buried within the protein [11].…”
Section: Pqc Degradation In the Nucleusmentioning
confidence: 99%